TRANSIENT ANALYSIS OF LAMINATED PLATES IN THERMAL ENVIRONMENT - Sadiq, Ibtehal Abbas; Majeed, Widad Ibraheem (Journal of Applied Engineering Science, 2024)
Transient displacement of laminated plates under combined load based on Mantari’ s displacement field are investigated. The solution is implemented under transient mechanical load (sinusoidal, step and triangular sinusoidal distributed pressures pulse) and thermal buckling for plates with different layer orientation and thickness ratio. Equations of motion based on higher-order theory are derived through Hamilton’s principle, and solved using Navier-type solution for simply supported laminated plates. The results are presented for many effective parameters such as the number of laminate and orientation on the dynamic response of plates. Results show the validity of this displacement field in studying response of laminated thick and thin plates under varied transient loading and design parameters.